DINAMIKA PUBERTAS ANTARA IBU DAN ANAK - Ismiyati Ismiyati; Darti Rumiatun; Suryo Ediyono (Jurnal Medikes (Media Informasi Kesehatan), 2022)
Many adolescents express fear, embarrassment and confusion when experiencing menstruation for the first time. They state that Puberty is an unpleasant experience. They do not understand that it is a physiological process. In conditions like this, the role of the mother is needed in helping adolescents identify Puberty. 62% of young women stated that their mother was their main source of knowledge about reproductive health. This study aimed to discover children's curiosity about Puberty and mothers' concerns in providing communication about Puberty. The method used is descriptive. The research respondents were mothers with daughters aged 9-10 years, with a total sample of 43 people. The study found that as many as 62.8% of girls had asked their mothers about Puberty or the body changes they were experiencing. Mother is the closest person for young women. However, 46.5% of mothers still feel worried about conveying or providing education about Puberty to young women. Mothers' worries can also be caused by communication barriers in discussions with their children, prevailing norms, the existence of several myths, and feelings of insecurity or embarrassment.